Audit Quality and Financial Performance of Listed Healthcare Firms in Nigeria - Uyaiabasi U. Frank (INTERNATIONAL JOURNAL OF ECONOMICS AND FINANCIAL MANAGEMENT, 2026)
This study examines the effect of audit quality on the financial performance of listed healthcare firms in Nigeria. In recent years, the credibility of financial reporting has become increasingly important for ensuring efficient resource allocation and enhancing corporate performance. High audit quality is expected to improve the reliability of financial statements, reduce information asymmetry, and strengthen investor confidence, thereby influencing firm performance. However, empirical evidence on this relationship remains mixed, particularly in emerging economies and sector-specific contexts. The study adopts an ex-post facto research design and utilizes panel data obtained from the annual reports of selected healthcare firms listed on the Nigerian Exchange Group over the period 2015 to 2024. Audit quality is proxied by earnings quality, measured using absolute discretionary accruals based on the Modified Jones Model, while financial performance is measured using return on assets (ROA). Panel regression techniques, including pooled ordinary least squares, fixed effects, and random effects models, are employed, with the Hausman test used to determine the appropriate model. The results indicate that audit quality has a positive and statistically significant effect on financial performance, suggesting that firms with higher-quality audits exhibit improved profitability. The findings support the argument that credible financial reporting enhances operational efficiency and reduces opportunistic behavior. The study concludes that audit quality plays a critical role in improving financial performance in the Nigerian healthcare sector. It recommends that regulatory authorities strengthen audit oversight mechanisms and encourage practices that enhance audit quality, while firms should prioritize high-quality audit engagements to improve financial outcomes.